Membrane Currents in Airway Smooth Muscle: Mechanisms and Therapeutic Implications - Luke J Janssen (Canadian Respiratory Journal)
Electrophysiological and pharmacological techniques were used to characterize the membrane conductance changes underlying spasmogen-evoked depolarization in airway smooth muscle (ASM). Changes included a transient activation of chloride ion channels and prolonged suppression of potassium ion channels; both changes are triggered by release of internally sequestered calcium ion and in turn cause opening of voltage-dependent calcium channels. The resultant influx of calcium ions contributes to contraction as well as to refilling of the internal calcium ion pool. Bronchodilators, on the other hand, act in part through activation of potassium channels, with consequent closure of calcium channels. The tools used to study ion channels in ASM are described, and the investigations of the roles of ion channels in ASM physiology (autacoid-evoked depolarization and hyperpolarization) and pathophysiology (airway hyperresponsiveness) are summarized. Finally, how the relationship between ion channels and ASM function/dysfunction may relate to the treatment of asthma and related breathing disorders is discussed.